The use of non-steady state noise interferences to counteract passive eavesdropping devices - Serhiienko, S.P.; Krizhanovski, V.G.; Chernov, D.V.; Zagoruiko, L.V. (Radiotekhnika, 2021)
The use of noise interference has become a common practice for information security. Recently appeared publications showing a potential possibility to use the noise radio frequency interference for information skimming by passive radio eavesdropping device. In particular, the vulnerability of the premises protected from eavesdropping devices is increased, if the radio frequency noising is switched on when confidential negotiations are being conducted. The use of radio noise waves energy for eavesdropping makes such devices invisible to nonlinear locators for listening devices if they activated only by noise signals. The paper shows that the use of non-steady state noise allows counteracting the unauthorized pickup of information. The analysis of non-steady state radio frequency noise effectiveness was carried out using the correlation receiver model. The correlation receiver has the highest sensitivity, and it works more efficiently with noise-like signals. It is shown that for counteracting the information pickup, it is necessary to use a noise, amplitude modulated by a random signal, whose spectrum coincides with a spectrum of a potential informational signal. Imposition a more powerful modulation noise to a weak informational signal makes impossible the information transfer. It is shown on the example of changing the power of a monochromatic signal while “beetle” transmits using steady-state and non-steady state noises, that due to the signal energy parametric redistribution over the non-steady-state noise modulation spectrum, the power of monochromatic signal is reduced by more than 10 dB compared to the transmission of the same signal using a steady-state noise. It can be concluded that the use of non-steady state noise signals for radio frequency suppression makes impossible their use for passive eavesdropping devices operation.